HUBUNGAN PERHATIAN ORANG TUA DENGAN SIKAP TOLERANSI SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Ridha Putri; Yustia Suntari; Chrisnaji Banindra Yudha (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2026)
This study aimed to examine the relationship between parental attention and tolerance attitudes among fifth-grade elementary school students. A quantitative correlational design was employed. The respondents were 31 fifth-grade students at SDN Pademangan Timur 01. Data were collected using questionnaires measuring parental attention and students’ tolerance attitudes and were analyzed using the Pearson Product Moment correlation. The results showed a positive and significant relationship between parental attention and students’ tolerance attitudes, with a correlation coefficient of 0.708 and a significance level of p < 0.001. This finding indicates that students with higher parental attention scores tended to have higher tolerance attitude scores. The coefficient of determination was 50.1%, indicating that variation in students’ tolerance attitude scores was statistically associated with variation in parental attention scores by 50.1%, while the remaining 49.9% was associated with other factors outside the variables examined. Therefore, parental attention represents one context associated with students’ tolerance attitudes. The findings highlight the importance of collaboration between families and schools in supporting students’ social and character development through communication, guidance, role modelling, and learning experiences that value differences. Keywords: Parental Attention, Tolerance Attitudes, Character Education, Elementary School Students.